Variations in Hedgehog signaling: divergence and perpetuation in Sufu regulation of Gli - Ruel, Laurent (Cold Spring Harbor Laboratory Press, 2009)
The Hedgehog (Hh) proteins play a universal role in metazoan development. Nevertheless, fundamental differences exist between Drosophila and vertebrates in the transduction of the Hh signal, notably regarding the role of primary cilia in mammalian cells. In this issue of Genes & Development, Chen and colleagues (pp. 1910–1928) demonstrate that mouse Suppressor of fused (Sufu) regulates the stability of the transcription factors Gli2 and Gli3 by antagonizing the conserved Gli degradation device mediated by Hib/Spop in a cilia-independent manner.